GLABELLAR FLAP RECONSTRUCTION FOR DEFECTS BELOW MEDIAL CANTHUS - Georgi Balchev; Georgi Yordanov; Snezhana Murgova (Journal of IMAB, 2024)
Background: Glabellar plastic is a method used for reconstructing the medial defects that use the available surrounding tissue, and in particular, that of the glabellar region. Most authors are of the opinion that this plastic is suitable for defects that reach the medial canthal area and do not pass down to the lower eyelid. Aim: To present the glabellar flap technique as an option for the reconstruction of defects that extend below the medial canthus, which is an application outside the recommended indications of this technique. Results: The postoperative outcome was good in all patients. Positional anomalies are within the limits of functional comfort. None of the patients requested postoperative cosmetic correction of the surgical defect. Conclusion: We demonstrated the possibility of using this technique below the level of the medial canthus. It carries risks for the appearance of positional abnormalities of the eyelids after surgery, but if the influence of laxity, skin texture and shape of the operative defect is properly taken into account, this technique provides a good alternative to combined surgery.